ANALYSIS OF LOW SEISMICITY (M (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
The Armenian highlands are characterized by the presence of potentially seismic zones that form the level of seismic hazard in the territory of the RA. In particular, the Van earthquake (M=7.2) in October 23, 2011 manifested in Yerevan by seismic shaking (J=5–6 points). The article presents the analysis of the seismic-geodyna-mic situation of the study area during the preparation of this strong earthquake. The first stage of the analysis is devoted to the study of low seismicity (M
Keywords: seismic shaking; low seismicity; seismological data; seismic focus; strong earthquake preparation